BANK LOANS AND FINANCIAL MANAGEMENT: HOW TO OBTAIN LOANS FROM FINANCIAL INSTITUTIONS BY CONSIDERING CREDIT SCORES AND STRUCTURED BUSINESS PLANNING FOR EFFECTIVE FINANCIAL MANAGEMENT - Eiras, Talyta Padrão (Revista Sistemática, 2022)
Obtaining bank loans is a critical aspect of financial management for entrepreneurs seeking to establish or expand their businesses. This article examines the processes involved in acquiring loans from financial institutions, emphasizing the importance of maintaining a strong credit score and developing a structured business plan. Effective financial management requires a proactive approach to credit improvement, transparent financial record-keeping, and strategic planning to demonstrate business viability to lenders. By addressing these factors, entrepreneurs can enhance their chances of securing financing and achieving sustainable business growth.